PEMBENTUK ATMOSFER TRADISIONAL PADA RESTORAN PESONA KAMPUNG SUNDA - Nazhar, Ryanty Derwentyana (Narada : Jurnal Desain dan Seni, 2024)
Pesona Kampung Sunda Restaurant integrates a variety of interior design elements inspired by the cultural heritage of West Java, including flooring, walls, ceilings, decorations, and furniture. The traditional atmosphere of Kampung Sunda is reflected from the entrance, courtyard, bale-bale (terrace), to the kitchen designed to resemble a pawon (traditional Sundanese kitchen). This study is significant in documenting and preserving cultural heritage within the business sector and in fostering innovative interior design that emphasizes local culture. The research aims to analyze how traditional Sundanese design elements are applied in creating a homey and village-like ambiance in the restaurant. A descriptive-analytical method was employed, with Pesona Kampung Sunda Restaurant in Bandung as the object of study. The research specifically focused on areas integrating traditional Sundanese elements to create an atmosphere aligned with the restaurant's identity. Data were collected through site surveys, visits to Kampung Naga, and interviews with representatives from both the restaurant and the Kampung Naga community. Findings reveal that the restaurant's interior design extensively references traditional elements from Kampung Naga and the surrounding areas of Garut. Most furniture and utensils are used according to their original functions, while others are decorative. This multisensory approach, involving texture, aroma, and sound, effectively creates a distinctive Sundanese ambiance, enhancing visitor interest and attraction.